Lateral Ankle Sprains and Their Association with Physical Function in Young Soccer Players - Murata K; Kumai T; Hirose N (Dove Medical Press, 2021)
Kenichiro Murata,1 Tsukasa Kumai,2 Norikazu Hirose2 1Graduate School of Sport Sciences, Waseda University, Nishi-tokyo, Japan; 2Faculty of Sport Sciences, Waseda University, Saitama, JapanCorrespondence: Norikazu HiroseFaculty of Sport Sciences, Waseda University, 2-579-15, Mikajima, Tokorozawa, Saitama 359-1192, JapanTel/Fax +81 42-451-1022Email toitsu_hirose@waseda.jpPurpose: Lateral ankle sprain (LAS) in childhood can result in lateral malleolus avulsion fractures; additionally, bone nonunion may occur. Physical maturity relates to the development of bone morphology and physical functionality. It is unknown how changes in physical functionality attributable to physical maturity affect young soccer players with abnormal lateral malleolus (ALM) morphology. Hence, the present study aimed to investigate the bone morphology of the lateral malleolus in young soccer players and to examine its relationship with physical functionality at different maturity levels.Subjects and Methods: Two hundred and ninety young soccer players aged 6– 15 years were included. The presence of ALM was assessed using ultrasonography. The subjects were allocated to three groups based on physical maturity (Pre-, Mid-, and Post-peak height velocity age [PHVA]). The prevalence of ALM and the relationship between ALM and physical maturity were examined for body composition, foot pressure distribution, foot alignment, ankle mobility, and single-leg balance.Results: The prevalence of ALM was 17.6%. For physical maturity, the post-PHVA group showed a decrease in ankle dorsiflexion and eversion and an increase in one-leg hop distance compared to the Pre-PHVA group (P < 0.05). In the ALM group, the center of pressure during heel raising was distributed laterally in the Post-PHVA (P < 0.01), and the weight-bearing dorsiflexion angle was decreased in the Mid- and Post-PHVA (P < 0.05).Conclusion: In the Post-PHVA young soccer players, decreased ankle dorsiflexion and eversion and increased one-leg hop distance were observed. The ALM group exhibited lateral loading during heel raising in the Post-PHVA group and decreased weight-bearing ankle dorsiflexion angle in the Mid- and Post-PHVA groups. The findings indicate the importance of secondary prevention of LAS and ultrasonography. Prospective studies of LAS in young athletes are required in the future.Keywords: lateral ankle sprain, ultrasonography, physical maturity, physical function, soccer